2019
DOI: 10.3892/ol.2019.10801
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase RNF5 serves an important role in the development of human glioma

Abstract: The ubiquitin ligase ring finger protein 5 (RNF5) has previously been associated with the development of breast cancer. Patients with breast cancer and high RNF5 expression have been demonstrated to have a shorter survival time compared with patients with low RNF5 expression. However, the role of RNF5 in human glioma has not been determined. The present study analyzed the role of RNF5 in gliomas using bioinformatics analysis. The results revealed that RNF5 was differentially expressed in non-cancerous brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The degradation of intracellular proteins is mainly accomplished by the ubiquitin-proteasome system, and the ubiquitin-proteasome have strong selectivity for protein degradation [ 23 ]. Studies have shown that the ubiquitination pathway is closely related to the occurrence and development of tumors [ 1 , 2 , 8 , 9 , 19 ]. Here we identified six differentially expressed URGs that were related to survival in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of intracellular proteins is mainly accomplished by the ubiquitin-proteasome system, and the ubiquitin-proteasome have strong selectivity for protein degradation [ 23 ]. Studies have shown that the ubiquitination pathway is closely related to the occurrence and development of tumors [ 1 , 2 , 8 , 9 , 19 ]. Here we identified six differentially expressed URGs that were related to survival in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitination pathway is a highly conserved post-translational modification process regulated by a series of enzymes [ 1 , 2 ]. It plays a leading role in the degradation of most proteins in eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RNF5 was able to degrade phosphoglycerate dehydrogenase (PHGDH), the first enzyme of the serine synthesis pathway, which is significantly upregulated in many cancers [ 14 ]. Finally, high expression of RNF5 in patients with glioma was associated with an improved prognosis compared to patients with low expression [ 15 ]. Given the controversial pathophysiological role of RNF5 in cancer, we extended the study of its functional expression to neuroblastoma (NB) and melanoma, which represent two neuroectodermal tumors of infancy and adulthood, respectively, with the same embryonal origin and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…RNF5 is a Ub E3 ligase, anchored to the endoplasmic reticulum (ER) membrane and crucial components of the ER-associated degradation (ERAD) process [ 71 ]. Based on the Cancer Cell Line Encyclopedia (CCLE) and TCGA database, mRNA expression level of RNF5 is abundant in AML compared to other cancer types, and there is a positive correlation between high RNF5 expression and poor survival [ 72 ].…”
Section: Ubiquitination In Amlmentioning
confidence: 99%